Green Cities : Sustainable Low-Income Housing in Brazil - World Bank (Washington, DC, 2013)
Housing development has direct and indirect impacts on the environment. Through its design, construction, and operation, housing represents a significant point of direct consumption of natural materials, water, and energy. Therefore, greenhouse gas emissions embodied in housing can be very significant. Moreover, in Brazil, civil construction is responsible for the largest percentage of solid waste volume generated in cities, resulting in additional environmental impacts. The housing sector also has substantial indirect environmental impacts associated with extended commuting distances from residents of housing developments and their resulting greenhouse gas emissions.The housing sector in Brazil offers substantial opportunities to improve enviromental performance. Housing developments, particularly large-scale low-cost programs, provide opportunities to minimize local and global environmental impacts through the use of energy efficient materials, design and construction guidelines, as well as performance standards. Many of these technologies and practices are appropriate to Brazilian conditions, and a number of them are already in use. Low-cost housing programs can be designed to incorporate sustainable materials and guidelines, with potentially large-scale impacts. With the launch of the Minha Casa, Minha Vida (MCMV) economic stimulus program to subsidize the construction of 1 million low-income housing units (and recent approval of a second round of subsidies for 2 million homes), Brazil is in a unique position to achieve the triumvirate of sustainable growth the social goal of reducing the national housing deficit, the economic stimulus goal of creating jobs in the construction industry, and the environmental goal of developing healthy homes and communities. Centralized funding sources like MCMV provide can be also used as models for other assisted housing programs and, potentially, market-rate housing developments as cities, developers and construction product manufacturers become more experienced in green housing technologies.Many green construction and technology programs are already in place. Brazil has a history of promoting programs and policies related to sustainable housing design construction and maintenance, such as product certification, supply-chain, research and development, and Green Building programs. The Selo Azul Program, launched by CAIXA in 2010 with the goal of promoting green housing development in Brazil, is particularly promising. Enhancements to current programs can greatly improve sustainability of housing sector. With increasing awareness on sustainable construction, there are currently major opportunities to promote the incorporation of green construction technologies, as well as hazard-resistant technologies for climate adaptation, within formal and informal low-income housing in Brazil. Based on a review of current practices at the national and international level, as well as on interviews with public and private sector practitioners, this Policy Note presents recommendations aimed at enhancing the sustainability of low-income housing approaches in Brazil, through the provision of high quality, energy-efficient housing with minimal environmental impacts.